Association between lifelines diet score with odds of nonalcoholic fatty liver disease and some novel anthropometric indices among adults: a case–control study - Asiaei, Sahar; Sharifani, Mohammad Sharif; Ghobadian, Bijan; Baghdadi, Ghazal; Biglari, Fereshteh; Rahimlou, Mehran (Frontiers in Nutrition, 2024)
BackgroundNonalcoholic Fatty Liver Disease (NAFLD) is a prevalent condition strongly associated with poor dietary habits and obesity. The Lifelines Diet Score (LLDS), a measure of adherence to a health-promoting diet, may reduce the risk of NAFLD. This study investigates the association between LLDS and NAFLD risk, as well as its relationship with novel anthropometric indices in adults.MethodsThis case–control study included 180 NAFLD patients and 250 controls aged 20–65 years from Valiasr Hospital, Zanjan, Iran. Dietary intake was assessed using a validated 147-item food frequency questionnaire, and LLDS was calculated by scoring food groups according to dietary guidelines. Anthropometric measurements included Body Mass Index (BMI), Waist Circumference (WC), A Body Shape Index (ABSI), Body Roundness Index (BRI), and Visceral Adiposity Index (VAI). Logistic regression models estimated the odds ratios (ORs) for NAFLD across LLDS quartiles.ResultsParticipants in the highest LLDS quartile had significantly reduced odds of NAFLD compared to those in the lowest quartile (OR = 0.49; 95% CI: 0.30–0.65; p < 0.001). Gender-specific analysis revealed that LLDS had a stronger inverse association with NAFLD in females (OR = 0.45; 95% CI: 0.29–0.64) than in males (OR = 0.63; 95% CI: 0.40–0.79). LLDS was inversely associated with VAI (β = −1.14; 95% CI: −2.89, −0.3; p = 0.036), but no significant associations were observed with ABSI or BRI.ConclusionHigher LLDS scores are associated with a lower risk of NAFLD and reduced visceral adiposity, particularly in females. These findings highlight the importance of improving dietary quality as a preventive strategy for NAFLD.